LPS-Induced Activation of the cGAS-STING Pathway is Regulated by Mitochondrial Dysfunction and Mitochondrial DNA Leakage in Endometritis - Li M; Wen X; Liu X; Wang Y; Yan L (Dove Medical Press, 2022)
Mu-zi Li,1- 5 Xiao-yang Wen,1- 5 Xiao-qiang Liu,1- 6 Yu-qing Wang,1- 5 Lei Yan1- 5 1Center for Reproductive Medicine, Shandong University, Jinan, People's Republic of China; 2Key Laboratory of Reproductive Endocrinology of Ministry of Education, Shandong University, Jinan, People's Republic of China; 3Shandong Key Laboratory of Reproductive Medicine, Jinan, People's Republic of China; 4Medical Integration and Practice Center, Shandong University, Jinan, People's Republic of China; 5Reproductive Hospital Affiliated to Shandong University, Jinan, People's Republic of China; 6Reproductive Medicine Center, Qingdao Women and Children's Hospital, Qingdao, People's Republic of ChinaCorrespondence: Lei Yan, Email yanlei@sdu.edu.cnIntroduction: Chronic endometritis is a common disease in women of childbearing age and can cause pelvic inflammatory disease. The cGAS-STING pathway plays an important role in many inflammatory diseases.Purpose: The aim of this study was to investigate the relationship between the cGAS-STING pathway and endometritis.Methods: We collected endometrium samples from patients with endometritis to detect changes in the cGAS-STING pathway. In vitro, human endometrial stromal cells (HESC) were stimulated with lipopolysaccharide (LPS), and a mouse STING gene-knockout model was established by CRISPR/cas9 for STING to further explore the mechanism underlying its effects in endometritis. We used Western blotting (WB) and immunohistochemical staining to detect the variations in protein levels and real-time PCR to study the variations in gene expression.Results: We observed the activation of the cGAS-STING pathway and an increase in the expression of cytokine-encoding genes, including IL-8, IL-6, IL-1β, and IFN-β 1, in endometrial tissues of patients with endometritis. Stimulation of HESCs using LPS demonstrated increase in the expression of proteins involved the cGAS-STING pathway and the gene expression of inflammatory cytokines. STING-knockdown experiments demonstrated a decrease in the gene expression levels of inflammatory cytokines. Moreover, we also identified the translocation of IRF3 and STING after LPS stimulation. Regarding mitochondrial function, LPS led to an increase in reactive oxygen species levels and a reduction in mitochondrial membrane potential. However, we observed that the mitochondrial DNA (mtDNA) leaked into the cytoplasm, upregulating the levels of proteins involved in the cGAS-STING pathway upon LPS stimulation. Furthermore, our results showed that LPS induced hyperemia, inflammatory factor production, and expression of Pho-TBK1 in wild-type mice compared with the levels in control mice, and STING gene-knockdown alleviated these effects.Conclusion: LPS induces mitochondrial dysfunction in endometrial stromal cells, resulting in mtDNA leakage and promoting endometritis by stimulating the cGAS-STING pathway.Keywords: endometritis, cGAS-STING, lipopolysaccharide, mitochondrial dysfunction, mitochondrial DNA, inflammatory factors